Differential recognition by the tumor suppressor protein p53 of DNA modified by the novel antitumor trinuclear platinum drug BBR3464 and cisplatin - Kasparkova, Jana; Fojta, Miroslav; Farrell, Nicholas; Brabec, Viktor (Nucleic acids research, 2004)
The trinuclear platinum agent BBR3464, a representative of a new class of anticancer drugs, is more potent than conventional mononuclear cisplatin [cis-diamminedichloroplatinum(II)]. BBR3464 retains significant activity in human tumor cell lines and xenografts that are refractory or poorly responsive to cisplatin, and displays a high activity in human tumor cell lines that are characterized by both wild-type and mutant p53 gene. In contrast, on average, cells with mutant p53 are more resistant to the effect of cisplatin. It has been hypothesized that the sensitivity or resistance of tumor cells to cisplatin might be also associated with cell cycle control and repair processes that involve p53. DNA is a major pharmacological target of platinum compounds and DNA binding activity of the p53 protein is crucial for its tumor suppressor function. This study, using gel-mobility-shift assays, was undertaken to examine the interactions of active and latent p53 protein with DNA fragments and oligodeoxyribonucleotide duplexes modified by BBR3464 in a cell free medium and to compare these results with those describing the interactions of these proteins with DNA modified by cisplatin. The results indicate that structurally different DNA adducts of BBR3464 and cisplatin exhibit a different efficiency to affect the binding affinity of the modified DNA to p53 protein. It has been suggested that different structural perturbations induced in DNA by the adducts of BBR3464 and cisplatin produce a differential response to p53 protein activation and recognition and that a 'molecular approach' to control of downstream effects such as protein recognition and pathways of apoptosis induction may consist in design of structurally unique DNA adducts as cell signals.
Keywords: Protein Binding; sekvence nukleotidů; adukty DNA; protinádorové látky; Consensus Sequence; Organoplatinum Compounds; nádorový supresorový protein p53; Response Elements; vazba proteinů; substrátová specifita; konsenzuální sekvence; Substrate Specificity; DNA Adducts; responzivní elementy; cisplatina; Base Sequence; organoplatinové sloučeniny; Cisplatin; Tumor Suppressor Protein p53; Antineoplastic Agents